Numerical and analytical study on the mechanical properties of a connector with long-fiber and metal laminated bolts for prefabricated construction. Issue 13 (October 2021) - Zhang, Xiaoming; Ren, Danni; Liu, Xin; Guan, Sujun; Yu, Xindi; Chen, Jinxinag; Nie, Chunlong
To improve the mechanical performances of joints in prefabricated construction, a type of connection structure with long-fiber and metal laminated bolts (referred to as a fiber-metal connector) is proposed and investigated by simulation and theoretical methods. The results include the following: (1) The fiber layer in bolts can form a second stiffness during rotation. This mechanical characteristic improves the bearing capacities and energy dissipation ability of the connector relative to the conventional metal connector, which are expected to effectively limit the elastoplastic rotational displacement of a structure. (2) For the reason, the fiber layer can bear load in the plastic phase due to its high-strength characteristic in the length direction. (3) A bilinear model for the bearing curve of the fiber-metal connector is proposed, and equations for optimization of fiber layer thickness are obtained with a target on bearing capacity and energy dissipation ability which are approximately higher 30% and 13% than that of the conventional metal connector, respectively. This research is expected to provide a theoretical basis for the application of this fiber-metal connector in engineering and improve the safety of prefabricated structures.